1963
DOI: 10.1002/pol.1963.100010905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high energy irradiation on polypropylene

Abstract: SynopsisIsotactic polypropylene (Profax) film samples irradiated in the Pennsylvania State University (PSU) reactor at ambient temperatures were examined by solvent extraction and infrared absorption techniques. At low irradiation doses, samples annealed (density = 0.909 g./cc. a t 24°C.) prior to irradiation were found to have a lower gel content and a higher concentration of oxidation products than quenched samples (density = 0.899 g./cc. a t 24OC.) irradiated under identical conditions. Similar gel fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1967
1967
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…If one uses a conversion factor of about 35 Mrad/lO" nvt," an estimate can be made of the correlation of changes observed by Chappell et al 9 and work presented herein. On this basis their sample which received a radiation dose of 3.2 X 10l8 nvt (reactor radiation) received a radiation dose of about 1100 Mrad.…”
Section: Polyamides Etc) S 5mentioning
confidence: 87%
See 1 more Smart Citation
“…If one uses a conversion factor of about 35 Mrad/lO" nvt," an estimate can be made of the correlation of changes observed by Chappell et al 9 and work presented herein. On this basis their sample which received a radiation dose of 3.2 X 10l8 nvt (reactor radiation) received a radiation dose of about 1100 Mrad.…”
Section: Polyamides Etc) S 5mentioning
confidence: 87%
“…DMP studies3 and the work of Chappell et al 9 indicate that high-energy irradiation of polypropylene produces crosslinking into a three-dimensional network accompanied by the destruction of the crystallites and a loss of rigidity. At lower doses where the crystallites were still present, it was reported that heat treatments at temperatures above the crystalline melting points tended to cause a decrease in density, while at higher doses, where the crosslinking density was higher and very few crystallites existed, a similar heat treatment caused an increase in density.…”
Section: Discussionmentioning
confidence: 99%
“…Also, high‐energy radiation can be used to enhance its thermal and chemical resistance. Because of this technological importance, the effects of γ‐radiation on the morphology and composition of polyethylene have been widely studied over the years by many investigators 1–22. However, it is difficult to obtain a full interpretation of the changes that polyethylene undergoes after high‐energy radiation exposure because different aspects take part in this process.…”
Section: Introductionmentioning
confidence: 99%